Expatriates' salary expectations, age, experience and country image - Duarte, H.; De Eccher, U.; Brewster, C. (Personnel Review, 2021)
Purpose: The purpose of this paper is to explain how candidates' expectations of salary in relation to job offers as expatriates in developing societies are related to country image and to age. Design/methodology/approach: Data were collected from over 500 engineers living in France, Portugal and Spain, evaluating two hypothetical expatriate proposals to six different African and Latin American countries. Multivariate hierarchical regression was applied to statistically detect significant predictors, with a broad range of control variables, to investigate expatriate salary expectations. Findings: Results evidence the role of age, seniority, previous international experience and culture attraction for the host country in influencing salary expectations for potential expatriate postings. These results are discussed at the light of selection, optimisation and compensation theory (SOC), conservation of resources theory (COR) and social identity theory. Practical implications: Findings call for multinational companies to consider age, individual background, career attributes and location concerns when evaluating salary expectations involved in expatriation to developing countries. Originality/value: The study shows how individual expectations about required salaries for accepting expatriate job offers in developing countries (hardly addressed in the extant literature) result from the potential for professional development opportunities and the responsibility of the jobs being offered, the country image, and the age and motivation of the individuals. Furthermore, it integrates research through use of SOC and COR theories.